1995
DOI: 10.1111/j.1365-2958.1995.tb02286.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of a chromosomal locus involved in copper tolerance in Escherichia coli K‐12

Abstract: The cutA locus, presumably involved in copper tolerance in Escherichia coli, was characterized by a mutation leading to copper sensitivity. Copper-accumulation measurements with radioactive 64Cu2+ showed increased uptake by cutA copper-sensitive mutant cells, and reduced uptake when the cutA mutation was complemented in trans. The locus was mapped using complementation of the cutA mutant to partial copper tolerance with wild-type chromosomal fragments. The 3.2 kb DNA region involved in cutA was sequenced and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
126
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(127 citation statements)
references
References 32 publications
(23 reference statements)
1
126
0
Order By: Relevance
“…Numerous attempts have been made to identify the genes involved in controlling copper levels in E. coli; however, few of these genes have been directly linked to copper metabolism, transport, or regulation (5,6). For instance, the nlpE (cutF) gene, which encodes for a novel lipoprotein, and dipZ (cutA2), which encodes for a disulfide isomerase, have indirect connections with copper metabolism (6,7).…”
mentioning
confidence: 99%
“…Numerous attempts have been made to identify the genes involved in controlling copper levels in E. coli; however, few of these genes have been directly linked to copper metabolism, transport, or regulation (5,6). For instance, the nlpE (cutF) gene, which encodes for a novel lipoprotein, and dipZ (cutA2), which encodes for a disulfide isomerase, have indirect connections with copper metabolism (6,7).…”
mentioning
confidence: 99%
“…Some studies have suggested that CUTA may play roles in copper tolerance/toxicity (20,40), AChE activity (18), signal transduction (21), etc. However, so far the exact functions of CUTA, especially those of human CUTA, remain largely undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…The trimeric core is preceded by a region of variable length with several variants in mammals (19). In bacteria, CutA is involved in copper tolerance, and some mutations in the cutA gene lead to copper sensitivity due to its increased uptake (20). Additional studies showed that many CutA proteins have a copper binding capacity and that copper could induce reversible aggregation of the CutA protein (21,22).…”
mentioning
confidence: 99%
“…2C), which is conserved across species from different taxa. In Escherichia coli the CutA protein is presumably involved in copper tolerance and also affects tolerance to zinc, cadmium, nickel, and cobalt salts (Fong et al 1995). A putative CpG island was identified on the 5Ј end of ntcon6.…”
Section: Identified and Mapped Genesmentioning
confidence: 99%
“…The encoded peptide showed similarity to the Arabidopsis thaliana CutA protein (Fong et al 1995; Fig. 2C), which is conserved across species from different taxa.…”
Section: Identified and Mapped Genesmentioning
confidence: 99%